Orthodontists’ preferences regarding the difference of bracket bonding height between the maxillary incisors - NASCIMENTO,Mauro Henrique Andrade (2021)
ABSTRACT Introduction: The vertical position of orthodontic brackets in maxillary incisors may influence the incisal step between the anterior teeth and thereby interfere with the smile esthetics. Even so, esthetic standards have been modified over time and consistently required technical adjustments. Objective: This study analyzed orthodontists’ preferences regarding the difference of bracket bonding height between the maxillary central incisors (MCI) and maxillary lateral incisors (MLI), and further determined whether the orthodontist sex, age and time of specialization have association to their choices. Methods: This study collected data through an electronic form. Study participants analyzed a clinical case in which they indicated their preference for bracket bonding height. The placement height options ranged from 3.0 mm to 5.5 mm from the incisal edge, with 0.5-mm intervals, or at the clinical crown center (CCC). The difference in the bonding height between the MCI and MLI was analyzed, considering the formation of incisal steps between these teeth. Results: Participants indicated that the difference in bracket bonding height between the MCI and MLI should be as follows: 0 mm (3.9%); 0.5 mm (78.3%); 1 mm (7.6%); 1.5 mm (0.2%); and CCC (9.9%). There was no statistically significant correlation between the choice for bracket bonding height and sex, age and time since specialization. Conclusion: Most participating orthodontists choose the 0.5-mm difference in bracket placement height between the MCI and MLI. The variables sex, age and time since specialization did not influence this choice.